2021
DOI: 10.3389/fonc.2021.760382
|View full text |Cite
|
Sign up to set email alerts
|

Dual Targeting of Multiple Myeloma Stem Cells and Myeloid-Derived Suppressor Cells for Treatment of Chemotherapy-Resistant Multiple Myeloma

Abstract: Here we review the insights and lessons learned from early clinical trials of T-cell engaging bispecific antibodies (BsABs) as a new class of biotherapeutic drug candidates with clinical impact potential for the treatment of multiple myeloma (MM). BsABs are capable of redirecting host T-cell cytotoxicity in an MHC-independent manner to malignant MM clones as well as immunosuppressive myeloid-derived suppressor cells (MDSC). T-cell engaging BsAB targeting the BCMA antigen may help delay disease progression in M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 80 publications
0
16
0
Order By: Relevance
“…The progress of human malignancies represented by the MM complex is often affected by the ECM or microenvironment ( 1 6 ). One sign of malignant transformation of these malignant tumor cells is metastasis and invasion, in which cells destroy the ECM/basal membrane of the primary site through MMPs and achieve invasive growth and migration to other tissues and organs ( 21 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The progress of human malignancies represented by the MM complex is often affected by the ECM or microenvironment ( 1 6 ). One sign of malignant transformation of these malignant tumor cells is metastasis and invasion, in which cells destroy the ECM/basal membrane of the primary site through MMPs and achieve invasive growth and migration to other tissues and organs ( 21 ).…”
Section: Discussionmentioning
confidence: 99%
“…Multiple myeloma (MM) is a clonal malignant plasma cell disease that accumulates in bone marrow, leading to bone destruction and marrow failure as well as out-bone injury for the whole body at advanced stages ( 1 3 ). Increasing data have been indicated that the MM is often accompanied by the multiple osteolytic lesions, hypercalcemia, or kidney damage ( 1 5 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Precision medicines as well as biotherapeutic agents, including therapeutic monoclonal antibodies such as the anti-CD38 MoAb Daratumumab and isatuximab, and the anti-signaling lymphocyte activation marker F7, antibody elotuzumab, antibody-drug conjugates, and bispecific antibodies (BiAb) have been developed to damage drug-resistant MM clones as well as alter the immunosuppressive bone marrow microenvironment with some very promising clinical data regarding their clinical impact potential [ 1 , 4 , 39 ] . T-cell redirecting BiAb and bispecific T-cell engagers (BiTES) targeting CD38, the orphan G protein-coupled receptor GPRC5D, and the B-cell maturation antigen (BCMA)/CD269 on MM cells and CD3 antigen on T-cells facilitate the CTL-mediated destruction of drug-resistant MM cells in cytolytic synapses [ 4 , 40 ] . They showed promising single-agent activity in early clinical trials of R/R MM patients, and risk mitigation strategies have been identified for their potentially serious side effects such as cytokine release syndrome and neurotoxicity [ 4 , 40 ] .…”
Section: Main Textmentioning
confidence: 99%
“…T-cell redirecting BiAb and bispecific T-cell engagers (BiTES) targeting CD38, the orphan G protein-coupled receptor GPRC5D, and the B-cell maturation antigen (BCMA)/CD269 on MM cells and CD3 antigen on T-cells facilitate the CTL-mediated destruction of drug-resistant MM cells in cytolytic synapses [ 4 , 40 ] . They showed promising single-agent activity in early clinical trials of R/R MM patients, and risk mitigation strategies have been identified for their potentially serious side effects such as cytokine release syndrome and neurotoxicity [ 4 , 40 ] . BCMA-targeting cellular immunotherapy platforms using chimeric antigen receptor (CAR)-T cells or NK cells have also been developed with documented objective clinical responses in single-agent trials [ 1 , 4 , 6 - 9 , 40 ] .…”
Section: Main Textmentioning
confidence: 99%